2022
DOI: 10.3389/fsurg.2022.867088
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis of the Jaw in COVID-19 Patients: A Rare Condition With a High Risk for Severe Complications

Abstract: Osteomyelitis of the jaw is an uncommon infection that arises from the flora of the oral cavity or sinuses and affects immunocompromised and polymorbid patients. Treatment includes surgical debridement and long regiments of broad-spectrum antibiotics. We present three cases of complicated jaw osteomyelitis presented with concurrent COVID-19 infection, including only two reported cases of odontogenic COVID-related osteomyelitis. The two mandibular cases were patients in their 30s with no comorbidities. The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Management of third molar pathology requires both accurate imaging 9 and appropriate surgical techniques to reduce the likelihood of developing complications and their manifestations [10][11][12][13][14][15] . Imaging analysis of the jawbone and condition of neighboring soft tissues requires correct understanding of the anatomy and the pathological effects on anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…Management of third molar pathology requires both accurate imaging 9 and appropriate surgical techniques to reduce the likelihood of developing complications and their manifestations [10][11][12][13][14][15] . Imaging analysis of the jawbone and condition of neighboring soft tissues requires correct understanding of the anatomy and the pathological effects on anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics, the global incidence of mandibular osteomyelitis is approximately 3-4 per 100,000 population [1]. Based its etiology, it can be classified into infectious and non-infectious osteomyelitis, with the majority of cases being caused by bacterial infections [2,3,4]. Previous studies have shown that bacteria can induce local abnormalities in bone metabolism, playing a significant role in the formation of necrotic bone However, whether local bacteria in mandibular osteomyelitis can also lead to systemic abnormalities in bone metabolism is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Osteomyelitis is defined as the inflammation of the either medullary, cortical, or cancellous bone, including nerves and blood vessels, causing necrosis and bone sequestrum formation (2,3). Odontogenic infections are considered the most frequent causative factor; however, other factors have also been observed in this disease: trauma, previous endodontic, periodontics infections, surgical procedures, radiation-based treatments, chemotherapeutic treatment, HIV, diabetes, anemia, leukemia, osteoporosis, malnutrition, Paget disease, fluorosis, and alcoholism (3)(4)(5). A clinical exploration will be always the best diagnostic tool; however, KEYWORDS: Actinomyces; Bilateral maxillectomy; COVID-19; Osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%